PENGGUNAAN MEDIA GAMBAR DAN KATA UNTUK MENINGKATKAN MAHARAH KITABAH DI SMP YPP NURUL HUDA SURABAYA - Jamilah, Mimi; Helmy Ismanto, Mohamad; Febriani, Rofika (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2021)
This study aims to determine whether there is a difference between student learning outcomes before and after being given treatment using pictures and words. It is assumed that there is a significant difference, as formulated in the research hypothesis that there is a significant difference between the increase in maharah kitabah for students after being given treatment using the picture and word method. The sample taken by the researchers amounted to 36 students. Data was collected by using the methods of interviews, observation, experiments, documentation, and tests. So far, the process of learning Arabic in class VII SMP YPP Nurul Huda Surabaya at maharah kitabah has been carried out using the Imla' method. So in this study, to increase the maharah of the book, the image and word media method was used. The aims of this study were (1) to determine the ability of the Arabic book maharah in the seventh grade students of YPP Nurul Huda School before the research was conducted. (2) To find out and describe the implementation of Arabic language learning in the maharah kitabah through the media of pictures and words in Class VII students of SMP YPP Nurul Huda Surabaya. (3) To find out and describe the increase in maharah kitabah in Grade VII students of SMP YPP Nurul Huda Surabaya. In this research, the writer uses quantitative data analysis method by using Mann – Whitney test with SPSS application. From the calculation results, it is found that the mean rank of the pre test is 24.01, and the mean rank of the post test is 48.99. This shows that there is a significant difference between the learning outcomes of maharah kitabah students in the experimental group before and after being given treatment using pictures and words.